The Need for Emergency Laparotomy With Open Abdomen Therapy in the Course of ECMO—A Retrospective Analysis of Course and Outcome - Schulz, Sissy-A.; Schaefer, Simone; Richards, Dana C.; Karagiannidis, Christian; Thomaidis, Panagiotis; Heiss, Markus M.; Bulian, Dirk R. (Frontiers in Surgery, 2020)
Background Abdominal Compartment Syndrome (ACS) can occur in patients placed on Extra Corporeal Membrane Oxygenation (ECMO). This implies the necessity of decompressive laparotomy followed by an open abdomen (OA) to prevent complications such as multi-organ-failure or death. Methods We searched for ECMO patients in our hospital data base between July 2015 and April 2020 and selected those with an emergency laparotomy and open abdomen therapy. Of these, we analyzed only patients who were treated with an open abdomen after establishing the ECMO regarding patient related parameters like sex, age, height, weight, and indications for ECMO as well as outcome parameters like complete fascial closure rate, mortality, length of stay in intensive care unit (ICU), length and kind of open abdomen therapy, number of surgical procedures, dressing changes concerning negative pressure wound therapy (NPWT), and number of surgical revisions. Results In eight out of 421 patients (1.9%) a laparostoma had to be created during ECMO support. For temporary closure, either NPWT, abdominal packing, or both, were used. The median length of open abdomen therapy was 17 days, the median length of stay in ICU was 42 days in total. The median number of surgical procedures and NPWT dressing changes was seven. In three of the eight patients, a surgical revision was necessary. The total mortality rate was 50%. In 75% the fascia could be closed. Two patients died before final closure. In all deceased patients an abdominal packing was necessary during the course of treatment, in the survivors only once. No enteroatmospheric fistula or abscesses occurred. Conclusions ACS in patients placed on ECMO is a very rare condition with a considerable mortality rate, but high secondary closure rate of the fascia. A necessary abdominal packing due to a severe bleeding seems to be a risk factor with a potentially fatal outcome.